A Study on Uric Acid Levels in Type 2 Diabetes Mellitus with Chronic Kidney Disease (Academia Journal of Medicine, 2020)
Background: The classification of stages of CKD is based on the level of kidney function measured by GFR, stage 1 represents kidney  damage with normal or elevated GFR and stage 5 represents a GFR of less than 15 ml/min or who require treatment with dialysis. In recent  times a new equation the Chronic Kidney Disease-Epidemiological Collaboration (CKD-EPI) has been introduced. The CKD-EPI equation has  lower bias, especially at an estimated GFR greater than 60 mL/min per 1.73 m2; however, precision remains limited. Subjects and Methods:  The study was undertaken in the Department Of General Medicine,and a total 64 CKD patients are included in study who fulfilled the  inclusion and exclusion criteria. These cases taken are not overlapped with other postgraduate students. The patients were randomly divided  into two groups according group chosen by time of enrollment. Results: The Study reveals that, there was no statistical significant difference  of mean serum uric acid among smokers and non-smokers in Type 2 diabetes mellitus with CKD(P>0.05). Conclusion: Study reveals that,  there was no statistical significant difference of mean serum uric acid among alcoholic and non-alcoholic cases in Type 2 diabetes mellitus  with CKD(P>0.05).
Keywords: Uric Acid Levels; Type 2 Diabetes Mellitus; Chronic Kidney Disease.